Category and Meaning Shift in Downfall (Der Untergang) Movie Subtitle from German into Indonesian - Nabila Larasati Putri Prasetya (Universitas Negeri Malang, 2021)
This study aims to describe category shift and meaning shift in movie’s subtitle Downfall (Der Untergang) directed by Oliver Hirschbiegel from German to Indonesian. The method used this study is contrastive qualitative. The sources of this study data are words, phrases, clauses, and sentences in Downfall (Der Untergang) movie’s from German into Indonesian subtitles. The data in this study are shifts, either category shift or meaning shift in Downfall (Der Untergang)from German and Indonesian subtitles. Methods used of acquiring data are listening methods with uninvolved conversation observation technique and taking note technique. The data are analyzed using distributional method and identity method simultaneously. While using distributional method, segmenting immediate constituents technique are used. In identity method, dividing key factors technique are used followed with the same interrelational method and the different interrelational method. The results of the study show that there are category shifts, namely 20 level shifts, 87 structure shifts, 23 class shifts, 132 unit shifts, 26 intra-system shifts, and meaning shift, namely 20 meaning shifts from generic to specific and vice-versa, and 22 meaning shifts from cultural point of view. In general, category shifts happened because there are structure, grammar, and system differences between source language and target language, while meaning shifts happened because of the difference of cultural point of view.